2021
DOI: 10.3390/pharmaceutics13030402
|View full text |Cite
|
Sign up to set email alerts
|

Ballodiolic Acid A and B: Two New ROS, (•OH), (ONOO−) Scavenging and Potent Antimicrobial Constituents Isolated from Ballota pseudodictamnus (L.) Benth.

Abstract: Bioassays guided phytochemical investigations on the ethyl acetate-soluble fraction of the root material of Ballota pseudodictamnus (L.) Benth. led to the isolation of two new compounds, ballodiolic acid A (1) and ballodiolic acid B (2), along with three known compounds ballodiolic acid (3), ballotenic acid (4), and β-amyrin (5), which were also isolated for the first time from this species by using multiple chromatographic techniques. The structures of the compounds (1–5) were determined by modern spectroscop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 46 publications
(28 reference statements)
0
5
0
Order By: Relevance
“…The compounds were tested for antibacterial activity against a number of bacterial species. At 30 μg/ml concentration, 25 and 26 exhibited the most potent antibacterial properties with ZOIs ranging between 11–13 and 11–12 mm, respectively, against E. coli and S. typhi strains ( Fozia et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The compounds were tested for antibacterial activity against a number of bacterial species. At 30 μg/ml concentration, 25 and 26 exhibited the most potent antibacterial properties with ZOIs ranging between 11–13 and 11–12 mm, respectively, against E. coli and S. typhi strains ( Fozia et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…Compounds 25 and 26 extracted from the roots of B. pseudodictamnus (L.) Benth [Lamiaceae] exhibited strong antifungal property. At 30 μg/ml concentration, 25 and 26 gave prominent antifungal activity, with % ZOIs ranging between 21% and 45% and between 25% and 47%, respectively, against different fungal strains compared to the standard drug miconazole (100%) ( Fozia et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…[33][34][35] ONOO À could alter the structure of various proteins, break DNA strands, and damage membrane structures via hydroxylation and oxidation reactions to speed up bacterial inactivation. [36][37][38] And generally, it is generated through an enzymeindependent reaction between NO and O À 2 in a physiological environment, 39,40 which proceeds so fast that O À 2 would preferentially react with NO instead of scavenging by SOD. 41 However, due to the short lifetime and diffusion distance of both O À 2 and NO, the in situ efficient formation of ONOO À becomes a big challenge.…”
Section: Introductionmentioning
confidence: 99%
“…Many plant-derived compounds have been used in the past because of their antimicrobial properties. Four studies in this Special Issue report the characterization of novel bioactive molecules and plant-derived biopolymers with strong antimicrobial properties [ 1 , 2 , 3 , 4 ]. Plants are also an important source of antioxidant peptides.…”
mentioning
confidence: 99%
“…Plants are also an important source of antioxidant peptides. In this volume, three publications investigated the antioxidant and ROS scavenging properties of plant-derived molecules [ 1 , 5 , 6 ]. Two of these studies by Cotabarren et al have also shown the isolation and characterization of thermostable peptides with anticoagulant properties [ 2 , 6 ].…”
mentioning
confidence: 99%